2017
DOI: 10.3168/jds.2017-13150
|View full text |Cite
|
Sign up to set email alerts
|

New potentially antihypertensive peptides liberated in milk during fermentation with selected lactic acid bacteria and kombucha cultures

Abstract: Compounds with the ability to inhibit angiotensin-converting enzyme (ACE) are used medically to treat human hypertension. The presence of such compounds naturally in food is potentially useful for treating the disease state. The goal of this study was to screen lactic acid bacteria, including species commonly used as dairy starter cultures, for the ability to produce new potent ACE-inhibiting peptides during milk fermentation. Strains of Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus delbrueckii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…In similar studies, antihypertensive properties of kefir‐fermented milk were showed to be in close dependence with peptides size and their proteolysis during product storage led to a sharp decrease in ACE inhibitory activity (Sanli et al ). Thus, it was reported a significantly higher ACE inhibition activity of milk peptides with MW lower than 10 kDa, compared to those with MW lower than 3 kDa (Elkhtab et al ). HPLC‐tandem mass spectrometry identified two hydrophobic peptides with sequences PYVRYL and LVYPFTGPIPN released from caprine kefir caseins, which showed high ACE inhibitory properties (Quiros et al ).…”
Section: Resultsmentioning
confidence: 99%
“…In similar studies, antihypertensive properties of kefir‐fermented milk were showed to be in close dependence with peptides size and their proteolysis during product storage led to a sharp decrease in ACE inhibitory activity (Sanli et al ). Thus, it was reported a significantly higher ACE inhibition activity of milk peptides with MW lower than 10 kDa, compared to those with MW lower than 3 kDa (Elkhtab et al ). HPLC‐tandem mass spectrometry identified two hydrophobic peptides with sequences PYVRYL and LVYPFTGPIPN released from caprine kefir caseins, which showed high ACE inhibitory properties (Quiros et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, whey fermented with Lactobacillus brevis produced a different peptide AEKTK, but also with ACE-I activity [62]. Additionaly, using Lactobacills casei and kombucha cultures resulted in 21 new peptides (6-18 amino acids in length) of which LVESPPELNTVQ, VLESPPELN, WGYLAYGLD were confirmed to have ACE-I activity [66].…”
Section: In Vitro Ace-i Activitymentioning
confidence: 99%
“…In a previous study, Lizardo et al (2020) [18] reported that mixed LAB-fermented cherry silverberry extract showed the effective production of viable lactobacillus compared to mono LABfermentation under harsh conditions such as acidity and low pH. In addition, the pH decreased and the cell counts increased during the LAB-fermentation of kombucha [26]. Mixed-fermentation with LAB strains using food materials contributed to higher survival rates than mono-fermented cells.…”
Section: Changes In the Total Soluble Solids Ph And Cell Countmentioning
confidence: 95%